EXAMINATION OF THE DEGREE OF SHRINKAGE AND SWELLING OF THE DOUGLAS FIR CELL WALL - Bardarov, Nikolay; Todorova, Martina; Todorov, Vladislav; Mollov, Viktor (Innovation in Woodworking Industry and Engineering design, 2024)
Upon sorption of water, wood swells, and this swelling can be directly measured at the macroscopic level of the scale. The reverse process is called shrinkage. The two processes are reciprocal and can be studied at different levels of scale. More difficult to observe and measure is the sub-microscopic level, i.e. how the cell wall swells and shrinks. There is a difference in the structure of the radial and tangential cell walls due to the different dynamics of the cambium division. The article studies the swelling and shrinkage of radial and tangential cell walls. An attempt has been made to model these processes geometrically at the cell level. Douglas fir early and late wood zones were studied.